Pelatihan Sistem Penyiraman Tanaman Otomatis IoT di SDN Gedangan 3 Sumobito Jombang - Mohamad Nasirudin; Sujono Sujono; Muhammad Nur Iman Nudin; Mokhammad Saifulloh Al Aziz; Riska Damayanti; Qurotul Ainiyah; Salim Ashar (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
This community service program was implemented at Public Elementary School Gedangan 3 in the rural district of Sumobito, Jombang, where school gardens support greening and environmental learning but plant care is constrained by manual, inconsistent watering. The project focused on introducing an automatic plant-watering system based on the Internet of Things using a soil-moisture sensor, a microcontroller, a relay, tubing, and a small water pump. The objectives were to motivate students’ interest in technology that benefits daily life, increase their knowledge of automatic watering principles and components, and provide direct practice operating a simple device. The approach combined participatory planning with teachers, structured instruction through presentation slides, a live demonstration of the device, guided student practice, and interactive discussion. Activities were conducted on 21 August 2025 with eighteen students from grades five and six, with classroom teachers acting as facilitators. Results showed improved student understanding of component functions and system operation, greater confidence and curiosity toward technology, and more consistent watering practices that support plant growth while using water efficiently. Students reported finding the learning enjoyable and accessible, and teachers indicated readiness to sustain the device for routine garden care. The program offers a practical, replicable model for integrating elementary-level technology literacy with environmental stewardship in school settings